Sistem Informasi Kepuasan Layanan Administrasi Akademik Berbasis IPA (Importance Performance Analysis) Studi Kasus Fakultas Teknik Universitas Mataram - Syaifullah Syaifullah; I Gede Pasek Suta Wijaya; Ario Yudo Husodo (Journal of Computer Science and Informatics Engineering (J-Cosine), 2018)
This paper presents a Satisfaction Information Systems of Academic Administration Services which is a tool to provide quality assessment of Academic Administration Services of Engineering Faculty, Mataram University. The quality assessment is determined by Importance Performance Analysis (IPA) method of survey data. This information system is designed and built by using CodeIgniter framework with PHP and HTML. The experimental results show that the proposed system has been running properly, which are indicated by a â€œfairly satisfiedâ€ achievement of Academic Administration Services of Engineering Faculty, Civil, Electrical, Mechanical and Informatics Engineering Dept. Based on MOS parameter on students (MOS = 4.45) and admin (MOS = 4.00), show that the system has been running properly.